Some notes on Sextus Empiricus’ method of approaching the téchnai - Brito, Rodrigo Pinto de; Skvirsky, Alexandre Arantes Pereira; de Morais, Lauro Iane (Revista Archai, 2017)
We aim to show how Sextus Empiricus develops his attack on the téchnai in Against the Professors (M I-VI). First of all, we will outline the concept of stoicheîon (plural: stoicheîa) in Aristotle, for we think that the wide use of the concept by the Hellenistic Philosophers addresses itself to Aristotle’s employment of it. Thus, Sextus Empiricus approaches the téchnai through a paradigm internal to their own systematization, from their “elements” (stoicheîa). Secondly, we will take into consideration Sextus’ approach to grammar, and we link this discussion on grammar to the other téchnai. Finally, we aim to identify the political and pedagogical consequences of Sextus’ approach.